2020
DOI: 10.15562/ism.v11i1.653
|View full text |Cite
|
Sign up to set email alerts
|

Profil onikomikosis pada pasien lanjut usia di Rumah Sakit Umum Pusat Sanglah, Bali, Indonesia: studi retrospektif

Abstract: Background: Fungal infections are one of the most common dermatologic conditions affecting elderly population. Elderly population is susceptible to all of the superficial mycoses such as tinea pedis, candidiasis, and onychomycosis in geriatric populations compared to other age groups.Objective:  To determine the profile of onychomycosis among elderly patients over a period of 1 years (January 2018–August 2019) at Dermatology and Venereology outpatient clinic, Sanglah General HospitalMethods:  Retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Anthropophilic dermatophytosis Trichophyton rubrum is the most common causative agent worldwide and is the cause of tinea pedis and tinea unguium 1,2 . The results of Karmila et al's research on elderly patients at Sanglah Hospital, Bali, Indonesia, reported that 40% of patients were infected with Trichophyton rubrum from culture examinations 3 . Another study of fish-slicing women in the Fisherman's Settlement in Bengkulu City, Indonesia, found that nine people (37.5%) out of 24 respondents were infected with Trichophyton rubrum 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Anthropophilic dermatophytosis Trichophyton rubrum is the most common causative agent worldwide and is the cause of tinea pedis and tinea unguium 1,2 . The results of Karmila et al's research on elderly patients at Sanglah Hospital, Bali, Indonesia, reported that 40% of patients were infected with Trichophyton rubrum from culture examinations 3 . Another study of fish-slicing women in the Fisherman's Settlement in Bengkulu City, Indonesia, found that nine people (37.5%) out of 24 respondents were infected with Trichophyton rubrum 4 .…”
Section: Introductionmentioning
confidence: 99%